Gradients of PI(4,5)P2 and PI(3,5)P2 Jointly Participate in Shaping the Back State of Dictyostelium Cells - Li, Dong; Sun, Feifei; Yang, Yihong; Tu, Hui; Cai, Huaqing (Frontiers in Cell and Developmental Biology, 2022)
Polarity, which refers to the molecular or structural asymmetry in cells, is essential for diverse cellular functions. Dictyostelium has proven to be a valuable system for dissecting the molecular mechanisms of cell polarity. Previous studies in Dictyostelium have revealed a range of signaling and cytoskeletal proteins that function at the leading edge to promote pseudopod extension and migration. In contrast, how proteins are localized to the trailing edge is not well understood. By screening for asymmetrically localized proteins, we identified a novel trailing-edge protein we named Teep1. We show that a charged surface formed by two PH domains in Teep1 is necessary and sufficient for targeting it to the rear of cells. Combining biochemical and imaging analyses, we demonstrate that Teep1 interacts preferentially with PI(4,5)P2 and PI(3,5)P2 in vitro and simultaneous elimination of these lipid species in cells blocks the membrane association of Teep1. Furthermore, a leading-edge localized myotubularin phosphatase likely mediates the removal of PI(3,5)P2 from the front, as well as the formation of a back-to-front gradient of PI(3,5)P2. Together our data indicate that PI(4,5)P2 and PI(3,5)P2 on the plasma membrane jointly participate in shaping the back state of Dictyostelium cells.